Interrelationship Features Between Emotional Intelligence And Satisfaction With Family Life (Zien Journal of Social Sciences and Humanities, 2025)
This article analyzes the relationship between emotional intelligence (EI) and the level of satisfaction with family life from a socio-psychological perspective. The study highlights the importance of empathy in family life quality, emotional regulation, communication culture, and interpersonal relationships. The results show that a high level of emotional intelligence is an important factor in increasing stability, positive climate, and satisfaction in family relationships.